Intrapleural Perfusion With Staphylococcal Enterotoxin C for Malignant Pleural Effusion: A Clustered Systematic Review and Meta-Analysis - Jiang, Hong; Yang, Xue-Mei; Wang, Cheng-Qiong; Xu, Jiao; Huang, Jun; Feng, Ji-Hong; Chen, Xiao-Fan; Chen, Kai; Zhan, Lin; Xiao, Xue; Xiao, Zheng (Frontiers in Medicine, 2022)
Introduction: The staphylococcal enterotoxin C (SEC), a commercially available bio-product from staphylococcus aureus (S. aureus) has been widely used to control MPE. Objectives: We designed and performed a new systematic review (SR) and meta-analysis to clarify the perfusion protocols with SEC, determine their clinical effectiveness and safety, and reveal the indication and optimum usage for achieving the desired responses. Methodology: All randomized controlled trials (RCTs) about SEC for MPE were collected from electronic databases (from inception until July 2021), and clustered into multiple logical topics. After evaluating their methodological quality, we pooled the data from each topic using the meta-analysis or descriptive analysis, and summarized the evidence quality using the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. Results: All 114 studies were clustered into SEC perfusion alone or plus chemical agents. The SEC alone showed a better complete response (CR), a lower pleurodesis failure and adverse drug reactions (ADRs), and a higher fever than cisplatin (DDP) alone. The SEC and chemical agents developed ten perfusion protocols. Among them, only SEC and DDP perfusion showed a better CR, a lower failure, disease progression and ADRs, and a higher fever than DDP alone. The SEC (100 ng to 200 ng per time, once a week for one to four times) with DDP (30 to 40 mg, or 50 to 60 mg each time) significantly improved clinical responses for patients with moderate to large volume, Karnofsky Performance Status (KPS) scores ≥ 40, ≥ 50 or ≥ 60, and anticipated survival time (AST) ≥ 2 or 3 months. Most results were moderate to low quality. Conclusion: Current evidences indicate that super-antigen SEC is a pleurodesis agent, which provides an attractive alternative to existing palliative modalities for patients with MPE. Among ten protocols, the SEC and DDP perfusion is a most commonly used, which shows a significant improvement in clinical responses with low ADRs. These findings also provide a possible indication and optimal usage for SEC and DDP perfusion.